2021
DOI: 10.1063/5.0070520
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-broadband THz/IR upconversion and photovoltaic response in semiconductor ratchet-based upconverter

Abstract: An ultra-broadband upconversion device is demonstrated by direct tandem integration of a p-type GaAs/AlxGa1-xAs ratchet photodetector (RP) with a GaAs double heterojunction light emitting diode (DH-LED) using the molecular beam epitaxy. An ultra-broadband photoresponse from the terahertz (THz) to near-infrared (NIR) region (4–200 THz) was realized, which covered a much wider frequency range compared with existing upconversion devices. Broadband IR/THz radiation from a 1000 K blackbody was upconverted into NIR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…We would also like to discuss some other approaches to the development of THz-to-IR converters. Bai et al 107 . demonstrated an ultrabroadband upconversion device, based on the integrated p-type GaAs/AlxGa1x As ratchet photodetector and GaAs double heterojunction LED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We would also like to discuss some other approaches to the development of THz-to-IR converters. Bai et al 107 . demonstrated an ultrabroadband upconversion device, based on the integrated p-type GaAs/AlxGa1x As ratchet photodetector and GaAs double heterojunction LED.…”
Section: Discussionmentioning
confidence: 99%
“…We would also like to discuss some other approaches to the development of THz-to-IR converters. Bai et al 107 demonstrated an ultrabroadband upconversion device, based on the integrated p-type GaAs∕Al x Ga 1−x As ratchet photodetector and GaAs double heterojunction LED. However, its photoresponse range, spanning from THz to NIR (4 to 200 THz), by far exceeded the frequencies suitable for biomedical research, e.g., 0.35 to 0.55 THz, capable to provide contrast margin of the cancerous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The high quality of homoepitaxial GaAs is required for e.g. spintronic devices, , ultra-height quality two-dimensional electron gas, an ultrabroadband upconversion device, or next-generation high-energy particle tracking detectors …”
Section: Introductionmentioning
confidence: 99%
“…The high quality of homoepitaxial GaAs is required for e.g. spintronic devices, 8,9 ultra-height quality two-dimensional electron gas, 10 an ultrabroadband upconversion device, 11 or next-generation high-energy particle tracking detectors. 12 In this work, we present procedure of initial growth parameters determination for obtaining homoepitaxial GaAs layers after MBE maintenance, which may standardize the process and minimize time to achieve the required outcome.…”
Section: Introductionmentioning
confidence: 99%
“…detectors attract more and more attention because they can obtain more information and are a crucial part of THz multicolor imaging and up-converter [4,5]. High-performance broadband THz detectors covering 1-10 THz are especially of great interest and is critically required for most application.…”
Section: Introductionmentioning
confidence: 99%